Experimental evaluation of ultrasonic oscillating temperature sensors (UOTS) under cyclically changing temperatures - Hashmi, Anas; Kalashnikov, Alexander N.; Light, Roger A. (2015)
In contrast to most conventional temperature sensors, which need to come to thermal equilibrium with the medium of interest to report its temperature, UOTS interrogate the medium based on the propagation speed of ultrasound, and will return temperature data that are “averaged” for the complete ultrasound pathway. It has been demonstrated that UOTS can provide consistent high-resolution temperature readings under steadily decreasing temperatures using inexpensive ultrasonic transducers and low cost electronic instrumentation.